UPAYA MENINGKATKAN HASIL BELAJAR PKn DENGAN PENERAPAN MODEL KOPERATIF SKRIP SISWA KELAS VI SDN 005 BUKIT KAPUR KECAMATAN BUKIT KAPUR - Abdullah ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this study is the low student learning outcomes Civics Class VI SDN 005 Bukit Kapur. This study aims to describe the results of learning by using the cooperative model script. The subjects were students of class VI SDN 005 Bukit Kapur consisting of two cycles. The data in this study focuses on improving learning outcomes. The instrument used for data collection is an oral test and a written test in the form of worksheets that do after the learning process. Results showed absorption learning outcomes on average 93% in subjects categorized Civics very good, very effective learning effectiveness categorized by an average of 93%. While completeness of student learning outcomes otherwise completed 100%.